Pengaruh Pelatihan dan Pengembangan Karir Terhadap Kinerja Karyawan Pada Toko Plastik di Kabupaten Sleman - Hanifah Hidayatul M; Kristiana Sri Utami (Universitas 45 Surabaya, 2024)
The aim of the research is to determine the effect of simultaneous and partial training and career development on employee performance at Plastic Shops in Sleman Regency. Efforts to realize optimal performance from an employee, of course, require training and career development programs so that there are no significant gaps in goals, measures and assessments. This research uses multiple linear data analysis methods using primary data obtained from questionnaires. The sample and research amounted to 21 people. The research results show that, with a t-value of 2.975 and a significant t-test value of 0.008 <0.05, training has an effect on employee performance. In the simultaneous test the F-count value was 20.740 with a significance of 0.000. Because the significance is less than 0.05, it can be concluded that training and development has a positive and simultaneous effect on employee performance at Plastic Shops in Sleman Regency.